Final report of excavations on the hill of the Ophel by R.A.S. Macalister and J. Garrow Duncan 1923-1925 : catalogue and examination of the finds in the collections of the Palestine Exploration Fund - Gilmour, Garth Hugh; Vincenz, Anna de, 1961-; Zimmerle, William G. (William Gerard); Amitai-Preiss, Nitzan (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Final Report of Excavations on the Hill of the Ophel by R.A.S. Macalister and J. Garrow Duncan 1923-1925 contains the publication of the finds from this excavation a century ago that have been curated and stored in the archives of the Palestine Exploration Fund in London. This volume includes a history of the excavation and detailed descriptions and illustrations of finds ranging from the Chalcolithic through to the Ottoman periods. These include pottery, metal, bone and glass objects, seal impressions, figurines, clay tobacco pipes and other items, many of which have never been published before. Among the more significant finds from the excavation, both the subject of special studies, are an incised pottery sherd with images of two deity figurines interpreted as representing Yahweh and Asherah, and two incense burners that contribute to our understanding of the trade in incense in the Near East in the second and first millennia BCE. This volume will be of interest to students and researchers of ancient near eastern archaeology, and particularly those engaged in research in the southern Levant. The report complements the publications of the many subsequent excavations in the same area of Jerusalem, a location that is still today the focus of much attention for historical, religious and political, not to mention archaeological, reasons"--
Introduction / Garth Gilmour -- Pottery from the Chalcolithic period to the Iron Age / Garth Gilmour -- Small finds from the Chalcolithic to the Roman period / Garth Gilmour -- The later periods / Anna De Vincenz, with contributions by Garth Gilmour and Nitzan Amitai-Preiss -- An Iron Age II sherd with a pictorial inscription illustrating Yahweh and Asherah : a special study / Garth Gilmour -- Incense burners : a special study / William Zimmerle.
Keywords: Macalister, Robert Alexander Stewart, -- 1870-1950.; Duncan, J. Garrow -- 1872-1951.; Excavations (Archaeology) -- Jerusalem; Jerusalem -- Antiquities; SOCIAL SCIENCE / Archaeology